Ovariectomy in mouflons under field conditions: a comparative assessment of midventral and flank laparotomy approaches - Frattina, Lorenza; Carbonari, Alice; Burgio, Matteo; Giannini, Francesca; Locantore, Francesco; Rizzo, Annalisa; Cicirelli, Vincenzo (Frontiers in Veterinary Science, 2024)
Ovariectomy is the best method to control the density of wild ungulate populations. The present study aimed to compare two surgical approaches of ovariectomy, via the flank and midventral, in mouflons under field conditions. A total of 20 female mouflons were enrolled in the study. The animals were divided randomly into two equal groups; group F animals were gonadectomized via the flank approach, while group L animals were sterilized via the linea alba access. The parameters evaluated were duration of surgery, duration of anesthesia, recovery time, intraoperative and postoperative complications, intraoperative nociception, and pain during the postoperative period. There were no intraoperative and postoperative complications. The evaluated parameters showed a very similar trend in both groups. Both techniques were found to be effective and safe in execution.